PENGELOLAAN PANTI ASUHAN SANTA MARIA: LAPORAN KEUANGAN USAHA DAN DESAIN RUANG KREATIF - Soejono, Fransiska; Mutika, Suzzana Winda Artha; Hermawan, Latius; Sunarni, Theresia; Anggraeni, Dhita Wahyu; Taslim, Jimmy; Romiya, Romiya; Oemar, Rexy (Jurnal Terapan Abdimas, 2019)
Abstract. Saint Mary’s Orphanage Pasang Surut is located in the Banyuasin Region of South Sumatra. The problem encountered today is the recording of financial statements that are simple using books and there are rooms that have not been used optimally. There is a need to redesign the room to fulfill the creativity of orphanage children. There are no human resources in the Panti who have the competence to create creative space designs. The solution to this problem is to conduct training activities on financial report making and creation of creative designs to optimize the use of one of the in-room spaces. The activity aims to improve the knowledge and skills of the institution manager and produce creative space design. The results of the activity are an increased understanding of financial reports and the use of Microsoft Office Excel to create business financial statements. The results of other activities are creative space design that is in line with the expectations of the institution manager.Keyword : Orphanage, Financial Report, Creative Room Abstrak. Panti Asuhan St. Maria Pasang Surut terletak di Daerah Banyuasin Sumatera Selatan. Permasalahan yang ditemui saat ini adalah pencatatan laporan keuangan yang sederhana menggunakan buku dan ada ruangan yang belum digunakan secara optimal. Ada kebutuhan untuk mendesain ulang ruangan untuk pemenuhan kreativitas anak-anak panti. Belum ada sumber daya manusia di Panti yang memiliki kompetensi untuk membuat desain ruang kreatif. Solusi dari masalah tersebut adalah dilakukan kegiatan pelatihan mengenai pembuatan laporan keuangan dan pembuatan desain kreatif untuk mengoptimalkan penggunaan salah satu ruang dipanti. Kegiatan bertujuan untuk meningkatkan pengetahuan dan ketrampilan dari pengelola panti dan menghasilkan desain ruang kreatif. Hasil kegiatan adanya peningkatan pemahaman tentang laporan keuangan dan pemanfaatan Microsoft Office Excel untuk membuat laporan keuangan usaha. Hasil kegiatan lainnya adalah desain ruang kreatif yang sesuai dengan harapan pengelola panti.Kata Kunci : Panti Asuhan, Laporan Keuangan, Ruang Kreatif